Perilaku Celebrity Worship Pada Penggemar K-Pop: Sebuah Kajian Literatur - Dewita Anjani, I Gusti Mutiara; Wulanyani, Ni Made Swasti (Jurnal Ilmiah Wahana Pendidikan, 2024)
Celebrity worship is a form of idolizing certain media figures, especially celebrities who have reached obsession. Based on several previous studies, it is known that the celebrity worship phenomenon is widespread among k-pop fans against their idols. This literature review aims to determine the things that affect celebrity worship, the description of celebrity worship behavior, and the impact of celebrity worship on k-pop fans. After extracting from 45 articles, 13 articles were obtained which were studied more deeply in this literature review. As a result, there are several things that influence celebrity worship on k-pop fans, namely big five personality, self-concept, self-control, religiosity, and attachment style. There are several things that become the impact of celebrity worship on k-pop fans, namely psychological well-being, impulsive buying, problematic internet use, cyberbullying, body image, and compulsive buying.